Microsoft PowerPoint 2010 on demand - Johnson, Steve, 1961- (On demand (Indianapolis, Ind.), 2010)
What you need, when you need it! Need answers quickly? Microsoft PowerPoint 2010 on Demand provides those answers in a visual step-by-step format. We will show you exactly what to do through lots of full color illustrations and easy-to-follow instructions. Includes Workshops MCAS Exam Prep More than 500 Essential PowerPoint Tasks Inside the Book: Create powerful presentations faster using ready-made templates; Organize information in sections and add impact with clip art, SmartArt diagrams, tables, and charts; Make your presentation come alive with custom animations, 3-D effects, and slide transitions; Embed, format, trim, and add text to videos in your presentation; Add comments and email your presentation to others for review; Broadcast your presentation over the Internet in a browser; Use SharePoint to collaborate and share documents; Prepare for the Microsoft Certified Application Specialist (MCAS) exam Bonus Online Content Register your book at queondemand.com to gain access to: Workshops and related files; Keyboard shortcuts.